2003
DOI: 10.1128/mcb.23.19.6750-6758.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant-Negative Thyroid Hormone Receptor Blocks Amphibian Metamorphosis by Retaining Corepressors at Target Genes

Abstract: The total dependence of amphibian metamorphosis on thyroid hormone (T 3 ) provides a unique vertebrate model for studying the molecular mechanism of T 3 receptor (TR) function in vivo. In vitro transcription and developmental expression studies have led to a dual function model for TR in amphibian development, i.e., TRs act as transcriptional repressors in premetamorphic tadpoles and as activators during metamorphosis. We examined molecular mechanisms of TR action in T3-induced metamorphosis by using dominant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 73 publications
5
78
0
Order By: Relevance
“…TRs bind TREs in the absence and presence of ligand (1). Most interestingly, in our studies on TR binding to TREs in vivo during metamorphosis by ChIP, we often observed variable amounts of TR binding to TRE of the TH-inducible TH/bZIP promoter, depending on the presence of ligand (15,25). To investigate the TH-dependent phenomenon, we treated premetamorphic tadpoles with or without 3,5,3Ј-triiodothyronine (T 3 ), a potent form of TH, and analyzed TR binding to two TH-inducible promoters, TR␤ and TH/bZIP, in the intestine and tail with anti-TR(PB) antibody (Fig.…”
Section: Tr Binding To Tres In Vivo Ismentioning
confidence: 75%
See 1 more Smart Citation
“…TRs bind TREs in the absence and presence of ligand (1). Most interestingly, in our studies on TR binding to TREs in vivo during metamorphosis by ChIP, we often observed variable amounts of TR binding to TRE of the TH-inducible TH/bZIP promoter, depending on the presence of ligand (15,25). To investigate the TH-dependent phenomenon, we treated premetamorphic tadpoles with or without 3,5,3Ј-triiodothyronine (T 3 ), a potent form of TH, and analyzed TR binding to two TH-inducible promoters, TR␤ and TH/bZIP, in the intestine and tail with anti-TR(PB) antibody (Fig.…”
Section: Tr Binding To Tres In Vivo Ismentioning
confidence: 75%
“…The destruction of larval organs and the formation of adult organs during frog metamorphosis is totally dependent upon TH (13,14). Transgenic overexpression of mutant TRs and cofactors showed gene activation by TR is necessary and sufficient to initiate TH-dependent developmental transitions in frogs (15,16). In knock-out mice lacking TRs, developmental defects are evident in brain, heart, and intestine, among other organs (17).…”
mentioning
confidence: 99%
“…Northern blot hybridization was done as previously described with a 32 P-labeled ST3 probe (43). RT-PCR was performed by using Superscript One-Step RT-PCR (Invitrogen) from 0.1 g of total RNA as described (44). RT-PCR for the transgene was done with the primers 5Ј-GGT ATC CTC ACC TGA TCA GTC AAG-3Ј (in the ST3 coding region) and 5Ј-CTT CAG CAC GTG TCT TGT AGT TCC-3Ј (in the GFP coding region).…”
Section: Methodsmentioning
confidence: 99%
“…Key players in this transition are the TH receptors, TR␣ and TR␤ (Schreiber et al, 2001;Buchholz et al, 2003Buchholz et al, , 2004. To investigate whether genistein affects TR␣ and TR␤ expression, tadpoles were injected with vehicle alone (DMSO) or T 3 and tail tips were cultured after 24 hr (24-hr injection) or 48 hr (48-hr injection).…”
Section: T 3 -Induced Up-regulation Of Tr␤ But Not Tr␣ Transcripts mentioning
confidence: 99%
“…TR␣ and TR␤ are the two major TR isoforms that possess dual functions as transcription repressors and activators in the absence and presence of ligand (primarily T 3 ), respectively (Sachs et al, 2000). Use of dominantnegative TR␣ (Schreiber et al, 2001;Buchholz et al, 2004) and dominantpositive TR␣ genes (Buchholz et al, 2003) in transgenic Xenopus laevis has shown that TR␣ is critical for T 3 -induced frog metamorphosis and for the regulation of known T 3 -response genes, such as TR␤, at the transcriptional level in the tail. TR␣ is present in the premetamorphic tadpole tail whereas TR␤ levels are extremely low until TH induction (Eliceiri and Brown, 1994;Veldhoen et al, 2002), suggesting that TR␣ is critical for the competence to respond to TH while TR␤ is required for establishment of the metamorphic genetic program.…”
Section: Introductionmentioning
confidence: 99%